Strengthening Qur'anic Literacy through Teachers' Integrated Pedagogical Roles - Lutvia Agustin; Anisatur Rohmah; Asfarinta Sakia Nor Fadhilla; Baiq Nila Maesaroh; Ishak Ishak (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
Improving Qur'anic literacy remains a major challenge for non-formal Islamic educational institutions, particularly in ensuring that students acquire not only accurate Qur'anic reading and writing skills but also sustained learning motivation and positive religious character. Although numerous studies have examined the effectiveness of Qur'anic learning methods, limited attention has been given to teachers' multidimensional pedagogical roles in strengthening students' Qur'anic literacy. This study aims to analyze the pedagogical roles of teachers in improving the quality of students' Qur'anic reading and writing at TPQ Al Muhajirin Karanglo Mojowarno Jombang, Indonesia. The research employed a qualitative case study design involving the head of TPQ, teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, non-participant observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that students' Qur'anic literacy develops progressively through continuous guidance, repetitive practice, and individualized feedback. Teachers perform integrated pedagogical roles as educators, instructors, motivators, mentors, supervisors, facilitators, and role models, creating meaningful learning experiences that enhance students' reading and writing competencies. Furthermore, family support, institutional commitment, and students' learning motivation significantly influence the effectiveness of Qur'anic learning. This study proposes an Integrated Pedagogical Framework for Qur'anic Literacy Development, emphasizing that improving Qur'anic literacy is achieved through the interaction between teachers' pedagogical competence, students' engagement, and supportive educational ecosystems. The findings contribute to the development of Qur'anic education theory and provide practical implications for strengthening teacher professionalism in non-formal Islamic education.